A study on the financial information disclosure mechanism of digital intelligence based on the participation of four parties - Yao, Jingjing; Sun, Yinan (Frontiers in Physics, 2025)
IntroductionThe digital era has brought about new vitality and innovation across various industries, introducing concepts such as AI, information centers, cloud data, the Internet of Things, and digital government. This article investigates the mechanisms of financial information disclosure within the context of digital transformation.MethodsA four-party game model is developed using a game approach, involving digitally-intelligent enterprises, financial data analysts, new quality productivity-based government, and fintech users. Through Matlab simulations, the evolutionary relationships and equilibrium game strategies among the four parties are examined.Conclusion(1) There are four conditional stabilization points in the four-way evolutionary game. These four conditional stabilization points represent the strategic equilibriums that stakeholders may achieve under the principle of competitive neutrality. They mainly reflect the strategic choices of the government and enterprises under different scenarios. (2) The numerical simulation analysis reveals that when the new quality productivity-based government will strengthen the regulation of the firm, it will force the firm to disclose information. And when the enterprise chooses to disclose information when disclosing financial information, then the government will relax the state of its regulation. This means that the government plays a stronger supervisory role in the process of corporate disclosure, which makes enterprises tend to increase the degree of information disclosure under external pressure, thus reducing information asymmetry and enhancing information transparency, which helps financial data analysts and fintech users to collect and organize information, and improves the stability of the market. The overall strategy evolves in the direction of “information disclosure, intelligent decision-making, intensive regulation, and investment”. (3) From the sensitivity analysis, the government’s influence on the utility of digital intelligence transformation is more significant, compared with other social actors, government departments show more significant institutional advantages in the digital intelligence transformation process; and the stronger the incentive and punishment mechanism imposed by the new quality productivity-oriented government, the strongest the reaction of enterprises in the societies studied in this paper; furthermore, it is found that there exists a bidirectional feedback mechanism between analysts and investors, and that when the poor market information environment leads to low investment intention of investors, it will make analysts reluctant to spend time and cost. Further, it is found that there is a two-way feedback mechanism between analysts and investors, when the poor market information environment leads to low investors' willingness to invest, it makes analysts reluctant to spend time, energy and cost on information processing.